PENGUATAN PENGETAHUAN KADER DALAM MENDAMPINGI IBU HAMIL PADA SITUASI BENCANA YANG DIPICU PERUBAHAN IKLIM - Padlilah, Rahmi; Farahdiba, Idha; Umami, Nurrahmi (Borneo Community Health Service Journal, 2025)
Attention, protection, and fulfillment of the needs of pregnant women during natural disasters must be provided in a specific and different manner compared to the general public or other disaster victims. Pregnant women affected by natural disasters will experience physical weakness as well as heightened concerns. In a disaster situation, pregnant women may experience stress, which will undoubtedly impact their pregnancy condition. In facing natural disasters, community involvement, such as that of cadres and community leaders, is very important. Due to the limitations of medical personnel, the involvement of cadres in supporting pregnant women is highly expected. Cadres, as part of the community, are individuals who are closely connected with pregnant women and also serve as drivers of public health development. The purpose of the community service is to increase the knowledge of cadres in accompanying pregnant women during disaster situations through education provided to the cadres in Kalampising Village, Lumbis District, Nunukan Regency, North Kalimantan Province. The participants in this activity numbered 15 people. The community service activity involved providing education about the role of cadres in accompanying pregnant women during disaster situations. The media used included PowerPoint, leaflets, and posters. The activity was held on Thursday, July 18, 2024, from 14:00 to 17:00 Wita, consisting of an opening and introduction, delivery of material, a question-and-answer session, and evaluation. The education provided new knowledge to the cadres, with the evaluation results showing that 86% of the cadres had good knowledge of the role of cadres in accompanying pregnant women during disaster situations.